Qadiyyah Ru’yatillāh fī al-Ākhirah Inda Al-Qādī ‘Abdul Jabbār wa Abī al-Hasan al-‘Asy’arī: The Issue of Seeing God in the Hereafter according to Al-Qādī ‘Abdul Jabbār wa Abī al-Hasan al-‘Asy’arī - Ma'afi, Rif'at Husnul; Adi Yatma, Rahmadani (University of Darussalam Gontor, Indonesia, 2024)
This article discusses the debate on the issue of ru'yatullah between Abu Hasan Al-Asy'ari who said that seeing God is something that is possible, this statement was then opposed by Alqadhi Abdul Jabbar he argued that it was something impossible, even though they used the same arguments for their respective opinions, and each of them has an interpretation of the verse. This incident happened because there were no definite arguments about the possibility of seeing God or not in the afterlife. Therefore, the dichotomy between groups in this discussion does not drop the status of infidels for those who disagree with them. This article uses a type of literature review with an aqidah approach and the method used is a descriptive method and an inductive method, and a comparative method to compare the two understandings and reveal some similarities and differences in their understanding. The result is that the researchers found several methods used by Al-Qadhi Abdul Jabbar in discussing Aqidah, namely prioritizing reason rather than naql, making reason as a proposition, rejecting khabar wahid and using arguments from ta'wil al kalamiy. Meanwhile, the method of Abu Hasan Al-Asy'ari in discussing the issue of Aqidah is mediating between naql and reason, using aqli arguments, accepting ta'wil al kalamiy. The view of Al-Qadhi Abdul Jabbar in ru'yatullah is of the opinion that Allah cannot be seen in this world or in the hereafter, in contrast to Abu Hasan Al-Ash'ari according to him the meaning of the word ru'yah is to know the knowledge and power of Allah, they believe that the people The believer will see his Lord on the Day of Resurrection even if he does not know how. Not through the ability to see that is found in the ordinary eye, but with the ability that is bestowed by Allah Swt.